Central corneal thickness and its relationship to myopia in Chinese adults. Issue 12 (17th August 2006) - Fam, H-B; How, A C S; Baskaran, M; Lim, K-L; Chan, Y-H; Aung, T
Abstract : Aim: To investigate the association between central corneal thickness (CCT) and the degree of myopia among Chinese. Methods: In this prospective observational study, 714 consecutive patients were recruited from a refractive surgery clinic. CCT was measured in both eyes of each patient using the Orbscan (Bausch and Lomb, Rochester, New York, USA), and data of the right eye were selected for analysis. CCT was correlated with the degree of myopia in dioptres (D) using Pearson's correlation coefficient and Dunnett's t test with multiple comparisons. Results: The age of the patients ranged from 15 to 59 years. The mean CCT was 534.5 μm, with a standard deviation (SD) of 38.1 (range 305–684) μm. The mean (SD) myopic spherical equivalent was 5.30 (2.74) D, range −17.5–−0.625 D. No correlation was found between CCT and the degree of myopia (r = −0.13, p = 0.719). Conclusions: Among Chinese with myopia, CCT was distributed over a large range but did not correlate with the degree of myopia.